Passenger Car Equivalents And Saturation Flow Rates For Through Vehicles At Signalized Intersections In Malaysia. - Lee Vien, Leong; Wan Ibrahim, Wan Hashim; Mohd Sadullah, Ahmad Farhan (2006)
Passenger car equivalents are used to represent the varying effects of mixed vehicle types on saturation flows by converting a traffic stream comprising of various vehicle types into an equivalent traffic stream comprising entirely of passenger cars.